The effect of gender and site on the condylar head measurements in Diyala - Mahdi Idan , Hayder (Diyala Journal of Medicine, 2024)
Background: The condylar process of mandible is an ellipsoid hard tissue (bony structure) with a thin neckline that joins to the mandibular ramus. The condylar processes are a critical anatomic component of the mandible that development of mandibular bone is attributed in the sagittal and vertical directions by condylar process. Objective: To radiographical assessment of condylar head measurements according to gender and site by uses cone beam computed tomography. Patients and Methods: The study samples consisted of sixty-five individuals (19 male and 46 female) with age range from (20-50) years old. Width of condylar head, length of condylar head and condylar head height were measured in the study by using cone beam computed tomography from radiology archive in specialist dental center in Diyala. Results: The results show condylar head width, condylar head height and condylar head length in sides (right and left), males have noted higher mean value than females. The results show condylar head width and condylar head length in left side, have recorded higher mean value than right side. While, condylar head height in left side, have recorded lower mean value than right side. Conclusion: Condylar dimensions and sizes may be associated with gender and site. Males have higher condylar dimensions and sizes than females.